Advances in nanotechnology for the treatment of GBM - Wei, Dongyan; Zhang, Ni; Qu, Shuang; Wang, Hao; Li, Jin (Frontiers in Neuroscience, 2023)
Malignant glioma is a malignant tumor of the central nervous system, and the mainstay of treatment is surgical resection, but because the demarcation between the margins of glioma and normal brain tissue is unclear, whether complete resection of glioma can be achieved or not depends on the empirical judgment of knife, there is a large error, which leads to a large probability of postoperative recurrence. Conventional radiotherapy, while killing tumor tissues, has large toxic side effects to normal tissues. Therefore, precise treatment and reducing toxic side effects are the irreducible treatment for malignant glioma. Nanomedicines have exhibited great potential in this regard and the rapid development of nanotechnology has provided many effective strategies for the diagnosis and treatment of malignant gliomas. In this review, relevant research progress in the utilization of nanotechnology for the diagnosis and treatment of malignant brain gliomas is reviewed to provide better options for developing new nanomedicine combinations and nano-diagnostics to combat malignant glioma.